The Finnish banking crisis and its handling (an update of developments through 1993) - Peter Nyberg; Vesa Vihriälä (Bank of Finland, 1994)
The paper is an update through early 1994 of a similarly titled paper (Bank of Finland Discussion Papers 8/93). It gives a brief description of the evolution of the Finnish banking crisis and its handling. In the first section, the salient features of the Finnish banking system are described. We then briefly discuss the liberalization process, macroeconomic and regulatory policies, and the subsequent credit boom and its development into a recession of unprecedented depth. Next, we document the impact on bank profitablity of the drastic changes in macroeconomic conditions. The collapse and rescue of, Skopbank are summarized. In section 2 we describe the public safety net, starting with the pre-crisis arrangements. This is followed by an exposition in section 3 of the, new measures taken in 1992 and 1993, with the emphasis on the establishment of the Government Guarantee Fund, its organization, powers and principles of operation. Section 4 gives an account of the support measures taken by the Goverment Guarantee Fund in the course of 1992 and the whole of 1993. Finally, in section 5, we discuss the banks' current economic environment and their prospects in the near future, now also brought forward into early 1994. The paper includes references to recent articles and discussion papers dealing with important aspects of the current banking crisis. The list of references is by no means exhaustive, and it is designed mainly to help foreign readers to find supplementary material. Therefore only those papers in Finnish or Swedish which have to do most with the current crisis are included.
URN:NBN:fi:bof-201501291032
Keywords: 330